2022
DOI: 10.3389/fphys.2022.800055
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Effects of Aldosterone and Hypokalemia on the Epithelial Na+ Channel and the NaCl Cotransporter

Abstract: Primary hyperaldosteronism (PA) is characterized by aldosterone excess and hypertension. This may be linked to increased renal Na+ reabsorption via the epithelial Na+ channel (ENaC) and the NaCl cotransporter (NCC). The majority of PA patients have normal plasma K+ levels, but a subset of cases are associated with hypokalemia. High NCC levels observed in long-term studies with aldosterone-infused rodents have been attributed to direct effects of aldosterone. Aldosterone can also increase active phosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…We observed an increase in γ -subunit protein in the aldosterone-alone treated group. Although against the commonly accepted role of aldosterone regulation in the kidney, our results support recently published studies showing changes in γ -ENaC expression with aldosterone, suggested to be caused by increased cell proliferation (Kristensen et al, 2022;Terker, Yarbrough, et al, 2016). Furthermore, we observed an increase in both βand γ -subunit message and protein in mice receiving HSD+Aldo.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed an increase in γ -subunit protein in the aldosterone-alone treated group. Although against the commonly accepted role of aldosterone regulation in the kidney, our results support recently published studies showing changes in γ -ENaC expression with aldosterone, suggested to be caused by increased cell proliferation (Kristensen et al, 2022;Terker, Yarbrough, et al, 2016). Furthermore, we observed an increase in both βand γ -subunit message and protein in mice receiving HSD+Aldo.…”
Section: Discussionsupporting
confidence: 90%
“…For the exact P values, the following abbreviations are used to denote groups being compared: C, control; S, high salt diet; A, aldosterone; SA, high salt diet with aldosterone. [Colour figure can be viewed at wileyonlinelibrary.com] to measure the length of the ENaC + tubule within our cleared kidneys as a result of poor antibody penetration, the study by Kristensen et al (2022), coupled with our finding of increased DCT2 length in HSD+Aldo treated animals, suggests that proliferation of the late DCT help explain our results.…”
Section: Figure 7 Dct Length Decreases With Aldosterone Alone But Inc...mentioning
confidence: 77%
See 1 more Smart Citation
“…[ 81 ]. In the present context, it is notable that recent evidence strongly supports the conclusion that effects of aldosterone and SGK1 on NCC are indirect and due to ENaC-dependent lowering of plasma [K + ], which stimulates NCC [ 32 , 79 , 166 ].…”
Section: The Aldosterone-mr-sgk1 Signaling Module Regulates Enacsupporting
confidence: 74%
“…They observed that whereas αENaC abundance was significantly downregulated in MR -/- cells, no differences in NCC or pNCC levels were observed either in baseline or low Na + diet conditions [11]. Third, Kristensen et al [12 ▪ ] recently showed that co-administration of amiloride with aldosterone to prevent the K + wasting induced by ENaC activation did not result in increased NCC and pNCC. Moreover, in isolated tubules that were incubated ex vivo with aldosterone for 21 h, no effects on NCC of pNCC were observed.…”
Section: Aldosterone Does Not Regulate Ncc Directlymentioning
confidence: 99%